Effect of Coal Combustion Waste on Cement-Treated Clay - Nugroho, Soewignjo A.; Wardani, S. P. Retno; Muntohar, A. S.; Satibi, Syawal (Civil Engineering Journal, 2024)
High plasticity clay is soil with poor material characteristics; one of them is the large shrinkage condition due to its high plasticity. Therefore, it is necessary to improve the soil using cement and coal-combustion waste (CCW). The purpose of this research is to determine the effect of mixture addition on the CBR value of the specimen on stabilization. Variations of 6%, 9%, 12%, and 15% of CCW and cement content vary by 3% and 5%. Based on the test results, there is an increment in the CBR bearing capacity, which was initially 0.80% to 18.75% to 42.90% by adding cement and CCW between 6% and 15%, respectively, after 7 days of curing. This increment is the largest of all variations in the CBR test. The percentage of increment in CBR value is quite large, i.e., a multiple of 200. This proves that the mixture is able to work effectively in increasing the bearing capacity of the soil. Based on microscopic testing of CBR samples, it is obtained that the higher the levels of Bottom Ash Fly Ash (BAFA) and cement, the rougher and paler the samples became as the structure changed. And vice versa, the lower CCW content and cement content made the sample structure become smoother and brighter in color, closer to the original color of natural clay. Doi: 10.28991/CEJ-2024-010-11-010 Full Text: PDF